Food allergy practical diagnosis and management - Sicherer, Scott H. (CRC Press, 2014)
Food allergy has increased over the past two decades, with a larger number of patients presenting a myriad of related symptoms and illnesses to physicians and allied health professionals. The growing number of patients poses a challenge to health care providers and confirms the need for developing best clinical practice guidelines. Based on the Expert Panel Report from the National Institute of Allergy and Infectious Diseases, Food Allergy: Practical Diagnosis and Management brings to life the developed guidelines with chapters written by international leaders in food allergy clinical care, research, and education, including most of the report's primary authors